About the Building Activities of Bishop Kapiton in Chersonesos – Cherson in the 4th century - Фомин, Михаил (Дриновський збірник, 2020)
The article is devoted to the issue of christianization of Chersonesus-Kherson of Late antiquity period and the activities of Bishop Capiton in construction. The city was an important center of the Roman Empire in the region and the issue of its christianization had not only religious and cultural, but also political significance in the early 80’s of the fourth century. The first attempt of baptising was made at the beginning of the century and led to clashes between pagans and Christians. Persecution continued for a long time, the evidence of which can be found in the monuments of the necropolis and the texts of the Lives of bishops of Chersonesus. Bishop Capito received support from the administration of the Empire, which allowed to stop the armed confrontation between Christians and their opponents (Jews and pagans) expelled from the city by Capito’s predecessor, Bishop Aetherius. St.Kapiton, having arrived in the city, entered into a dispute with the opponents of Christianity and a miracle “in the oven” was revealed by his prayer. After that, most of citizens were baptized, and the pagan complex on the Eastern Cape of the settlement was dismantled. Instead, the Basilica of the Apostle Peter was built. A delubrum, where citizens were baptized was built next to it. The complex of the Eastern Basilica was repeatedly rebuilt during its operation, which significantly changed its appearance. The final victory of Christianity in the city and the construction of the first major religious complex are associated with the activities of St. Bishop Capito. In the 6th century, during the “construction boom”, it was rebuilt and is known today in the literature as the “Eastern Basilica” complex.